2020
DOI: 10.1055/a-1206-0852
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a biopsy protocol to improve detection of esophageal eosinophilia: a Danish registry-based study

Abstract: Background In the North Denmark Region (580 272 inhabitants), only 0–4 cases of possible eosinophilic esophagitis (EoE) were identified annually in 1999–2010, suggesting underdiagnosis. This study aimed to increase the diagnosis of EoE by introducing a regional biopsy protocol for patients with dysphagia. Methods In 2011, leaders of regional endoscopy units attended a consensus meeting where a biopsy protocol was proposed. The national pathology registry was used to identify patients with esophageal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 28 publications
1
48
0
3
Order By: Relevance
“…DanEoE is a histopathology registry based cohort as previously described in detail. 9 It's based on the national "SNOMED" codes for topography and morphology of tissue. 10 All patients living in the NDR and for the first time having at least one biopsy coded with both the SNOMED code for esophagus mucosa (T62010) and inflammation with eosinophilia defined as 15+ � Despite the 50-fold increase in cases, the current study showed that the regions referring physicians and endoscopists lacked knowledge of EoE as patients had a mean diagnostic delay of 10 years, a total of one fifth of the patients were not treatment initially, and macroscopic signs of EoE were reported in less than half of inflamed patients.…”
Section: Definition Of the Study Population In Daneoe The Retrospective Database Of Oesophageal Eosinophiliamentioning
confidence: 99%
See 4 more Smart Citations
“…DanEoE is a histopathology registry based cohort as previously described in detail. 9 It's based on the national "SNOMED" codes for topography and morphology of tissue. 10 All patients living in the NDR and for the first time having at least one biopsy coded with both the SNOMED code for esophagus mucosa (T62010) and inflammation with eosinophilia defined as 15+ � Despite the 50-fold increase in cases, the current study showed that the regions referring physicians and endoscopists lacked knowledge of EoE as patients had a mean diagnostic delay of 10 years, a total of one fifth of the patients were not treatment initially, and macroscopic signs of EoE were reported in less than half of inflamed patients.…”
Section: Definition Of the Study Population In Daneoe The Retrospective Database Of Oesophageal Eosinophiliamentioning
confidence: 99%
“…-689 eosinophils (eos) in one high power field (hpf) (M47150) in 2007-2017 were included. 9 The index endoscopy was defined as the first endoscopy where the biopsy was sampled. In Denmark, every individual in the country is assigned a unique social security number and this is linked to the national population-based medical registries, including medical records, diagnostic codes, microbiology, biochemistry, and pathology findings.…”
Section: Definition Of the Study Population In Daneoe The Retrospective Database Of Oesophageal Eosinophiliamentioning
confidence: 99%
See 3 more Smart Citations